Efektivitas Penerapan E-Court Perkara Perceraian di Pengadilan Agama Parepare - Arifin, Harmina; L, Sudirman; Rahmawati, Rahmawati; Basri, Rusdaya; Fikri, Fikri (LPPM Universitas Ekasakti Padang, 2024)
The Supreme Court in an effort to apply one of the principles in civil law, namely the principle of simple, fast and light costs, has implemented the e-court system as stipulated in Supreme Court Regulation Number 1 of 2019 concerning Electronic Administration of Cases in Court. The purpose of this study was to determine the extent of the Effectiveness of the Implementation of E-Court Pekara Divorce in the Parepare Religious Court. This research is a descriptive qualitative research with a normative juridical approach with data collection through interviews and literature studies by searching literature, books, and legislation. The results of this study show that electronic proceedings at the Parepare Religious Court in 2022 are very effective. The supporting factors in electronic events include electronic event support facilities such as electronic media such as smartphones and PCs / laptops, internet networks, having active e-mail and telephone / whatsapp numbers, public awareness of the importance of electronic events and the importance of having the ability to use electronic media. The inhibiting factor of electronic events is the internet network, lack of technological knowledge. Analysis of the impact of the implementation of e-court this research is that the Parepare Religious Court as much as possible conducts socialization about e-court and its features to the community so that the use of e-court in the future can increase.